Fractal Characteristics and Energy Dissipation of Granite After High-Temperature Treatment Based on SHPB Experiment - Liu, Lei; Wang, Yuan; An, Huaming (Frontiers in Earth Science, 2022)
In deep mining and high-concentration nuclear waste storage engineering, the surrounding rocks may be subjected to the combined action of high-temperature fire and impact load. In this study, the fracture morphology and energy dissipation of granite following high-temperature treatment at 25–800 °C were analyzed using Split Hopkinson Pressure Bar (SHPB) device. The fracture characteristics and dynamic mechanical properties of granite were determined. The energy dissipation of granite specimens affected by high temperatures in the SHPB experiment was also analyzed. When the temperature of impact rate was less than 200 °C, the fragmentation degree, transmitted energy, and dissipated energy of granite increased with an increase in temperature. When the temperature was higher than 200 °C, the change law was opposite. A strong linear correlation existed between the fragmentation, fractal dimension, and energy consumption density of granite at different impact rates after high-temperature treatment. Moreover, a strong quadratic correlation existed between the damage factors and temperature. When the temperature was less than 200 °C, the damage factor decreased with the increase in temperature. When the temperature was higher than 200 °C, the change law was opposite, which corresponded with the influence law of temperature on dynamic compressive strength. Scanning electron microscopy and X-ray diffraction analyses were conducted to study the fracture modes and mineral composition changes in the granites. A quantitative relationship existed between macro - and meso-properties. The results could provide theoretical basis for the design of underground engineering structures, post-disaster assessment, and rehabilitation activities.